Picture-based insurance: Is it sustainable? Effects on willingness to pay, adverse selection, and moral hazard - Kramer, Berber; Ceballos, Francisco; Krupoff, Matthew; Toor, Mann S.; Mishra, Azad; Karekar, Siddesh; Robles, Miguel (International Food Policy Research Institute, 2017)
This project note hence describes to what extent picture-based crop insurance is viable from an economic point of view, addressing the following questions: (1) Do farmers strategically reduce crop management efforts (that is, does PBI induce moral hazard) and is there evidence of tampering with pictures in order to receive pay-outs when they have PBI coverage? (2) What is farmers’ willingness to pay for PBI compared to willingness to pay for standard weather index-based insurance (WBI)? Is farmers’ demand for PBI strong enough to justify its higher costs? (3) To what extent do farmers se-lectively enroll plots that are more prone to damage? In other words, is PBI prone to adverse selection?